A new maximum power point tracking technique based on whale optimisation algorithm for solar photovoltaic systems. Issue 1 (31st December 2022) - Premkumar, M.; Kumar, C.; Anbarasan, A.; Sowmya, R.
Abstract : In order to explore the highest allowable photovoltaic energy with high performance under a change in environmental situations, photovoltaic (PV) systems have to function at maximum peak power. This study outlines an efficient algorithm for maximum power point tracking (MPPT) to obtain maximum output from the photovoltaic module during partially shaded conditions (PSC). The suggested approach is based on the whale-optimisation (WO) algorithm and, with such a fast convergence speed and low tracking efficiency, this method seeks to identify the global peak (GP). This suggested methodology minimises the computation complexity confronted by the numerous literature-discussed MPPT algorithms and helps to reduce the oscillation of power throughout a change in environmental conditions. The suggested system is modelled in Matlab/Simulink and experimented with for various test cases. The simulation result proves that the WO algorithm can trace the GP effectively with less power fluctuation.